MOLECULAR SPECTROSCOPIC ANALYSIS OF THE FUNCTIONAL COMPOSITION OF SILK FIBRON - U. T. Asatov; M. A. Tulametov; Sh. N. Buribaev (European Science Publishing, 2025)
X-ray diffraction analysis of the samples showed that in the range of diffraction angles considered, crystalline reflexes were observed at 2θ=13.09°, 18.63°, 21.21°, 25.33° and 30.39°, which are characteristic of fibroin.
Keywords: Silk fibroin, x-ray, hydrolysis, micro and nano particles, spectrum.